Stock liquidity and corporate trade credit strategies: evidence from China - Shahzad, Umeair; Liu, Jing; Luo, Fukai (Journal of Business Economics and Management, 2022)
This study investigates the nexus of stock liquidity and trade-credit policies in China from 2002 to 2017. The estimates are robust to alternative proxies, various fixed-effects, and the exogenous impact of Chinese split share structure reforms (SSSR) 2005-06 is investigated through the difference-in-difference analysis. The results validate that stock liquidity significantly impacts firms’ capacity to produce more trade credit supplies and less reliant on trade credit demand. The study applied SUEST analysis to investigate the effect of the Chinese institutional setting. The nexus of stock liquidity and trade credit strategies is substantial in state-owned enterprises. Additional analysis revealed that the said association is more visible to credit-constrained and equity-reliant enterprises. The policymakers should focus on market liquidity because it elevates firms’ capacity to mobilize capital through trade credit provisions. The micro aspect of this study suggests that stock liquidity allows managers to shape non-price competitive strategies and avoid excessive usage of trade credits. First published online 30 November 2021